Chapter 12 Careful with heritage - Porciani, Ilaria (Critical Heritages of Europe, 2020)
Food Heritage and Nationalism in Europe contends that food is a fundamental element of heritage, and a particularly important one in times of crisis. Arguing that food, taste, cuisine and gastronomy are crucial markers of identity that are inherently connected to constructions of place, tradition and the past, the book demonstrates how they play a role in intangible, as well as tangible, heritage. Featuring contributions from experts working across Europe and beyond, and adopting a strong historical and transnational perspective, the book examines the various ways in which food can be understood and used as heritage. Including explorations of imperial spaces, migrations and diasporas; the role of commercialisation processes, and institutional practices within political and cultural domains, this volume considers all aspects of this complex issue.　Arguing that the various European cuisines are the result of exchanges, hybridities and complex historical processes, Porciani and the chapter authors offer up a new way of deconstructing banal nationalism and of moving away from the idea of static identities. Suggesting a new and different approach to the idea of so-called national cuisines, Food Heritage and Nationalism in Europe will be a compelling read for academic audiences in museum and heritage studies, cultural and food studies, anthropology and history. Chapters 1,2,4,6 and 12 of this book are available for free in PDF format as Open Access from the individual product page at www.routledge.com. They have been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license